MANAGEMENT OF SEPTIC SHOCK DUE TO COMMUNITY-ACQUIRED PNEUMONIA WITH CHRONIC KIDNEY DISEASE: A CASE REPORT - Arief Kurniawan,; Nur Pudyastuti Pratiwi, (Journal of Innovation Research and Knowledge, 2022)
Community-acquired pneumonia (CAP) is an infectious disease that causes local and systemic inflammation, resulting in a dysregulation of the body's reaction and life-threatening organ failure, also known as sepsis. Chronic kidney disease is a prevalent, progressive condition that has become a public health problem. Infection is the major cause of death and hospitalization in people with end-stage renal disease. Pneumonia is one of the most common infectious diseases, and it is linked to an increased risk of death and a lower glomerular filtration rate. A 49-year-old woman was diagnosed with uremic encephalopathy, chronic kidney disease with hyperkalemia, and community-acquired pneumonia. Antibiotics were chosen based on the risk of infection with Pseudomonas bacteria exposure, which included the possibility of bronchiectasis infection, corticosteroid treatment >10 mg/day, the use of broad-spectrum antibiotics for more than 7 days in the previous month, as well as the presence of malnutrition. This patient was found to have been infected with Pseudomonas bacteria. Ceftazidime and levofloxacin were chosen as antibiotics for this patient, as suggested by the Indonesian Intensive Care Doctors Association. Early identification, effective resuscitation, antibiotic therapy, and positive ventilation support when needed are all critical components of successful care of septic shock caused by community-acquired pneumonia. In individuals with renal failure, proper dosage adjustments will result in optimal therapeutic effects and fewer adverse effects.